An innovative approach to support interests' alignment in the context of transport management using semantic differential - Shpak, Nestor; Dvulit, Zoriana; Maznyk, Liana; Sroka, Włodzimierz; Podra, Olha; Petryshyn, Nataliia (My University, 2022)
PURPOSE: Our study aims to develop an innovative approach to scientific substantiation and practical balance of interests of cargo owners and transport companies, which will serve as a tool for freight management. METHODOLOGY: A specific algorithm of actions is proposed, which initially provides the creation of a system of indicators to study transportation management. The research methods include a complex method of semantic differential modeling, which integrates correlation-regression analysis, cluster analysis, and expert evaluations. The basis of such a complex method is the integration of three components: i) a system for monitoring the satisfaction of consumers of transport services; ii) the assessment of the density of connections between cargo turnover by type of transportation and the leading transportation indicators; iii) a multidimensional assessment of the homogeneity of factors by hierarchical clustering. FINDINGS: Semantic differential modeling can serve as an effective tool in strategic planning, not only for transport companies and railway enterprises, but also for those institutions where it is necessary to identify the most important areas of activity. IMPLICATIONS: The use of semantic differential based on the involvement of quantitative methods of mathematical modeling allows increasing the degree of validity of management decisions. The harmonization and balancing of interests in the field of B2B take into account the results of modeling the semantic differential in management. The proposed methodology consists of main indicators of rolling stock transportation and certain economic indicators; we advise to focus on. These indicators were obtained through cooperation with an expert group of participants in the transportation process. Application of the created model allows defining priority directions in the field of freight owners’ service by the Ukrainian railways in the dynamics by types of cargo and transportation and substantiating the corresponding management decisions by freight carriers. ORIGINALITY AND VALUE: Innovation is a complex interdisciplinary integration of research methods based on the philosophy of semantic differential, allowing the integration of approaches to harmonize the interests of transport companies and consumers of their services with the results of cooperation in the field of freight transportation. Therefore, the developed innovative methodology can be used not only for railway transport but also for other types of transport and business. МЕТА: Наше дослідження спрямоване на розробку інноваційного підходу до наукового обґрунтування та практичного балансу інтересів вантажовласників і транспортних компаній, який слугуватиме інструментом управління вантажними перевезеннями. МЕТОДИКА: Запропоновано конкретний алгоритм дій, який на початковому етапі передбачає створення системи показників для дослідження управління транспортом. Методи дослідження включають комплексний метод семантичного диференційного моделювання, який поєднує кореляційно-регресійний аналіз, кластерний аналіз та експертні оцінки. В основі такого комплексного методу лежить інтеграція трьох компонентів: і) системи моніторингу задоволеності споживачів транспортними послугами; ii) оцінка щільності зв'язків між вантажообігом за видами перевезень і провідними показниками перевезень; iii) багатовимірна оцінка однорідності факторів шляхом ієрархічної кластеризації. ВИСНОВКИ: Семантичне диференціальне моделювання може слугувати ефективним інструментом стратегічного планування не тільки для транспортних компаній і залізничних підприємств, а й для тих установ, де необхідно визначити найважливіші сфери діяльності. ЗАСТОСУВАННЯ: Використання семантичного диференціалу на основі залучення кількісних методів математичного моделювання дозволяє підвищити ступінь обґрунтованості управлінських рішень. Гармонізація та балансування інтересів у сфері B2B враховують результати моделювання семантичного диференціалу в менеджменті.Запропонована методика складається з основних показників перевезень рухомим складом та окремих економічних показників; радимо зосередитися на. Ці показники були отримані завдяки співпраці з експертною групою учасників транспортного процесу. Застосування створеної моделі дозволяє визначати пріоритетні напрямки у сфері обслуговування вантажовласників залізницями України в динаміці за видами вантажів і перевезень та обґрунтовувати відповідні управлінські рішення перевізниками. ОРИГІНАЛЬНІСТЬ ТА ЦІННІСТЬ: Інновація – це комплексна міждисциплінарна інтеграція методів дослідження, заснована на філософії семантичного диференціалу, що дозволяє інтегрувати підходи до гармонізації інтересів транспортних компаній та споживачів їхніх послуг з результатами співпраці у сфері вантажних перевезень. Тому розроблена інноваційна методика може бути використана не тільки для залізничного транспорту, а й для інших видів транспорту та бізнесу.
Keywords: кафедра економіки праці та менеджменту; semantic differential; freight transport; cluster analysis; correlation-regression analysis; гармонізація інтересів; семантичний диференціал; вантажні перевезення; кластерний аналіз; кореляційно-регресійний аналіз; transport management; управління транспортом